2020
DOI: 10.3390/ma13040876
|View full text |Cite
|
Sign up to set email alerts
|

Use of A Hydroalcoholic Extract of Moringa oleifera Leaves for the Green Synthesis of Bismuth Nanoparticles and Evaluation of Their Anti-Microbial and Antioxidant Activities

Abstract: The employment of plant extracts in the synthesis of metal nanoparticles is a very attractive approach in the field of green synthesis. To benefit from the potential synergy between the biological activities of the Moringa oleifera and metallic bismuth, our study aimed to achieve a green synthesis of phytochemical encapsulated bismuth nanoparticles using a hydroalcoholic extract of M. oleifera leaves. The total phenolic content in the M. oleifera leaves extract used was 23.0 ± 0.3 mg gallic acid equivalent/g o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…1c). Das and coworkers recently revealed that BiNPs had a distinctive absorption peak at 270 nm, which is almost identical to the absorption band found in our study [24]. Similarly, a prior study found a UV-Vis absorption peak at 285 nm in nanometer-sized bismuth particles [27].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1c). Das and coworkers recently revealed that BiNPs had a distinctive absorption peak at 270 nm, which is almost identical to the absorption band found in our study [24]. Similarly, a prior study found a UV-Vis absorption peak at 285 nm in nanometer-sized bismuth particles [27].…”
Section: Resultssupporting
confidence: 90%
“…Row 12 was used as a control (medium and bacterial inoculums). Following the incubation period, each well of the microtiter plate was filled with 30 mL (0.015%) resazurin solution and incubated at 37°C for 2 to 4 h to observe color change [20,23,24]. MBC was also calculated by collecting the contents of wells in three plates with concentrations greater than the MIC value.…”
Section: Preparation Of Standardized Inoculum and 96mentioning
confidence: 99%
“…Antioxidant activity of Moringa oleifera bark aqueous extract (BEM) and MgONPs was evaluated through (2,2-diphenyl-1-picrylhydrazyl) DPPH radical testing in accordance with the procedure described by Das et al [29], using ascorbic acid as reference. DPPH 0.1 mM solution is was prepared by dissolving in ethanol.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Different methods are used to qualitatively test phytochemical compounds contained in moringa oleifera (BEM) extracts. The test method used refers to the report Das et al [29], Qualitative evaluations of several chemical contents are shown in Table 1. Table 1 shows BEM containing phytochemical compounds such as alkaloids, flavonoids, saponins, and phenolics.…”
Section: Phytochemical Screening Of M Oleifera Bark Aqueous Extractmentioning
confidence: 99%
See 1 more Smart Citation